Opioid-induced adrenal insufficiency: diagnostic and management considerations - Patel, Erica; Ben-Shlomo, Anat (Frontiers in Endocrinology, 2024)
The dramatic rise in opioid use over the last two decades has led to a surge in their harmful health effects. Lesser known among clinicians is the impact of opioids on the endocrine system, especially with regard to cortisol. Opioids can suppress the hypothalamus-pituitary-adrenal (HPA) axis and may result in clinically significant adrenal insufficiency, especially in those treated at higher doses and for a longer time. A high clinical suspicion is necessary in this population for early diagnosis of opioid-induced adrenal insufficiency (OAI). Diagnosis of OAI is challenging, as the symptoms are often vague and overlap with those due to opioid use or the underlying pain disorder. Traditional assays to diagnose adrenal insufficiency have not been widely studied in this population, and more investigation is needed to determine how opioids might affect assay results. Once a diagnosis of adrenal insufficiency has been made, glucocorticoid replacement in the form of hydrocortisone is likely the mainstay of treatment, and effort should be made to taper down opioids where possible. Cortisol levels should be retested periodically, with the goal of stopping glucocorticoid replacement once the HPA axis has recovered. In this review, we provide context for diagnostic challenges in OAI, suggest diagnostic tools for this population based on available data, and offer recommendations for the management of this disorder. There is a paucity of literature in this field; given the widespread use of opioids in the general population, more investigation into the effects of opioids on the HPA axis is sorely needed.